Prosedur penjanaan idea menggunakan teknik sumbang saran untuk kursus eksplorasi reka bentuk tekstil di Universiti Teknologi MARA Malaysia / Rainal Hidayat Wardi - Rainal Hidayat , Wardi (2016)
This thesis presents and introduces an empirical model of idea generation for textile design in Universiti Teknologi MARA (UiTM) through the integration of brainstorming techniques required for teaching textile design. This model is called I-BRAINTEX (Integrated Brainstorming for Textile Design Ideation) acting as a procedure for textile design idea generation thus helps teaching and learning process (T&L). I-BRAINTEX has two objectives, namely the idea generation for creative design ideas and problem solving in textile design process. Through I-BRAINTEX, these ideas can be generated with an emphasis on the quantity and quality of ideas thus facilitating the construction of the project design theme. Three brainstorming techniques were applied as an idea generation technique specifically for textile design. At the first stage, individual brainstorming and mind map techniques were used as preparation to stimulate initial ideas related to research subject that suitable with design project theme. Individual brainstorming was intended as pre-knowledge enrichment before undergoing group brainstorming session. In the second stage of idea generation, group brainstorming techniques used for the generation, development and exploration of ideas through the contribution of ideas from group members. The objective of this technique was divided into two, namely the generation of ideas in large quantities and refinement of quality ideas. Group brainstorming is also known as creativity in groups that also to promote collaborative Teaching and Learning approach (T&L). Group brainstorming technique is very practical to be applied together with sketching skills to strengthen the ideas. In the third stage of idea generation, group brainwriting technique was used for the purpose of improvement of group brainstorming by determining the quantity of ideas that need to be achieved without compromising the quality of ideas. All the proposed brainstorming (individual brainstorming, group brainstorming and brainwriting) was viewed as idea generation and comprehensive problem solving for textile design. The results of this study show that the three brainstorming techniques have a high significance towards creativity achievement through T-Test analysis and it is practical approach for teaching and learning textile design. This study was also found that I-BRAINTEX is managed to achieve the objective of quantity and quality of ideas and suitable to serve as idea generation model for textile design.